مظاھر الحیاة العقلیة والأدبیة في الشعر العباسي: Manifestations of intellectual and literary life in Abbasid poetry - Dr. Hamid Ashraf Hamdani (International Research Journal of Arabic and Islamic Studies, 2025)
The Abbasid period is unanimously considered to be a golden era in the history of Arabic literature. In this period, Arabic literature with its different forms of prose and various genres of verse was in full bloom. This article deals with different phenomena of rational as well as literary life of the Arabs, in the light of poetry composed in Abbasid period. The mutual confrontation of the Allavid and the Abbasid, tribal and national dispositions and tendencies, literary discussions of poets, battles, translations, influence of other culture, pedagogic poetry, innovation in meter and rhyme are the topics of import which can rightly be called basic components of rational and literary life of the Abbasid period.